Discontinuous stereotactic body radiotherapy schedule increases overall survival in early-stage non-small cell lung cancer. (July 2021) - Duvergé, L.; Bondiau, P.-Y.; Claude, L.; Supiot, S.; Vaugier, L.; Thillays, F.; Doyen, J.; Ricordel, C.; Léna, H.; Bellec, J.; Chajon, E.; de Crevoisier, R.; et al.
Highlights: Aim: To evaluate the benefit of discontinuous SBRT schedule on local control (LC) and overall survival (OS) in NSCLC patients. Results: OS and LC were significantly higher for patients treated with a discontinuous schedule compared to a continuous one. Interpretation: SBRT for early-stage NSCLC should be done leaving one day off between the consecutive fractions. Abstract: Objectives: The duration of stereotactic body radiotherapy (SBRT) for early-stage non-small cell lung cancer (NSCLC) may affect patient outcomes. We aimed to determine the impact of a continuous versus discontinuous SBRT schedule on local control (LC) and overall survival (OS) in NSCLC patients. Materials and methods: Consecutive NSCLC stage I patients (475) treated with SBRT in four centers were retrospectively analyzed. The delivered dose ranged from 48 to 75 Gy in 3–10 fractions. Based on the ratio between the treatment duration (TD) and number of fractions (n), patients were divided into two groups: continuous schedule (CS) (TD ≤ 1.6n; 239 patients) and discontinuous schedule (DS) (TD > 1.6n; 236 patients). LC and OS were compared using Cox regression analyses after propensity score matching (216 pairs). Results: The median follow-up period was 41 months. Multivariate analysis showed that the DS (hazard ratio (HR): 0.42; 95 % confidence interval (CI): 0.22–0.78) and number of fractions (HR: 1.24; 95 % CI: 1.07–1.43) were significantly associated with LC. The DS (HR: 0.67; 95 % CI: 0.51–0.89), age (HR: 1.02; 95 % CI: 1–1.03), WHO performance status (HR: 2.27; 95 % CI: 1.39–3.7), and T stage (HR: 1.4; 95 % CI: 1.03–1.87) were significantly associated with OS. The 3-year LC and OS were 92 % and 64 % and 81 % and 53 % for DS and CS treatments, respectively (p < 0.01). Cox analysis confirmed that the discontinuous SBRT schedule significantly increased LC and OS. Conclusion: DS is associated with significantly improved LC and OS in early-stage NSCLC patients treated with SBRT.